2013
DOI: 10.1002/jor.22473
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of hypercoagulability genetic polymorphisms in perthes disease

Abstract: Perthes disease is an osteonecrosis of the femoral epiphysis with unclear etiology. This study aimed to systematically review the association between genetic determinants of hypercoagulability (Factor V Leiden, prothrombin II, and methylenetetrahydrofolate reductase; MTHFR) and Perthes disease. PubMed and Scopus searched from inception to January 2012, data extraction and quality assessment were performed. The odds ratio (OR) for the allele effect was pooled, and heterogeneity and publication bias were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 29 publications
2
29
0
1
Order By: Relevance
“…Numerous studies have indicated that disruption of the blood supply to the femoral head is a key pathogenic event resulting in bone necrosis (2,21,22). Thrombophilia and/or decreased fibrinolysis are possible mechanisms that have been investigated as potential causes of LCPD (23)(24)(25). It may be speculated that sequence variations in the eNOS gene could influence nitric oxide production, and thereby affect the progression of LCPD.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have indicated that disruption of the blood supply to the femoral head is a key pathogenic event resulting in bone necrosis (2,21,22). Thrombophilia and/or decreased fibrinolysis are possible mechanisms that have been investigated as potential causes of LCPD (23)(24)(25). It may be speculated that sequence variations in the eNOS gene could influence nitric oxide production, and thereby affect the progression of LCPD.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, studies relying on the use of EHR data are thought to have greater external validity, having drawn their participants from actual patients receiving regular care in actual health care settings. In such studies, however, participants must be chosen based not only on the eligibility criteria but also upon the availability of sufficient data for extraction [17-19]. Example sufficiency requirements include “a sub-population who have sufficient health record data at institution {X} frequenting the {X} hospital system for routine care” and “total number of individuals that have male gender and serum creatinine 1.5 mg/dL or female gender and serum creatinine 1.3 mg/dL.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis[47] held in 2012 investigated factor V Leiden, prothrombin II and methylenetetrahydrofolate reductase (MTHFR) polymorphism as sources of possible genetic aetiology of LCPD. They comprised 12 case-control studies, including 824 children in the Perthes group and 2033 children in the control group.…”
Section: Resultsmentioning
confidence: 99%